The Gutenberg parenthesis the age of print and its lessons for the age of the internet - Jarvis, Jeff 1954- (Bloomsbury Academic, 2023)
"As we begin to leave the Gutenberg age, and into a era dominated by the Internet, we have much to learn from how we transitioned into the age of print and how it changed how we think and communicate"--
Keywords: Geschichte; Druckmedien; Buchdruck; Printing / History